(3NGJe SdjeGfs - (3HdRGc, ChfhQjg Ojs; (3YHO Gddg, Uhajs ((3GdbGgQIs (3CbdGe YQHjI ddfTQ hGdJhRjYs, 2019)
(3JMcj GdQhGjI Yf TGH WGeY VGb Hg GdabQ, aVGb HGdMjGI hSNW Ydi GdbOQ Cfg de jefMg eG efM GdeMXhXjf ef GdKQGA hGdfahP, aacQ aj JQc GdOfjG haLCI jdYH GdeDda dYHJg GdHGQYI (B.. (3MjK jaJQV WdSeG SMQjG jefM UGMHg GdbOQI Ydi JMbjb Ci TF jWdHg hdcf HKef (B.(3R gPG GdKef gh GdGfJbGU ef CjGe YeQgs
(3GdcJGH eJQLe ef GddZI GdaQfSjIs
Keywords: (3GdCOH GdaQfSjs; (3GdeJQLeGJs